MAJOR DEPRESSIVE DISORDER WITHOUT PSYCHOTIC SYMPTOMS IN CHILDREN UNDER THE AGE OF 14 YEAR-OLD RAPE VICTIM. - Metrisiawan, Andika (E-Jurnal Medika Udayana; vol 3 no 2 (2014):e-jurnal medika udayana)
Depression is a very large impact on the global disease that affects people worldwide. Lately, an estimated 350 million people suffering from depression. The World Mental Health Survey in 17 countries stated that 1 in 20 people who reported experiencing a depressive episode in the last 1 year. Depressive disorders often appear early in life and causes a decrease in a person's interest and often recurrent. For this reason it is said that depression is the leading cause of disability in relation to total annual loss due to disability. Therapy should be given a basic psychosocial support combined with antidepressant medication or psychotherapy such as cognitive behavioral therapy, interpersonal psychotherapy or problem-solving treatment. This case report discusses the severe depression without psychotic symptoms in children under the age of 14 year-old rape victim. In addition to the victim made an approach to the development of psychological 1 therapy is also given in the form of Psychotherapy and Pharmacotherapy ie 1 x 20 mg fluoxetine oral and Benzodiazepine 1 x 10 mg orally.
Keywords: Depression, children, rape victim